Poétique de l’ananas - Frédéric Tinguely (Viatica)
This article examines the description of the pineapple as a strategic locus in the Histoire d’un voyage faict en la terre du Brésil (1578) by Jean de Léry. It attempts to show that this description reflects in some ways, like a magnifying mirror, the poetics of the entire work: from the taste for order to the choice of native names, from the use of analogies to the representation of sensorial experience, both rich and ephemeral. Léry’s specificity is regularly revealed through the confrontation with previous testimonies on "the most excellent fruit" of the New World, in particular those of Gonzalo Fernández de Oviedo and André Thevet.